Serial order working memory and numerical ordinal processing share common processes and predict arithmetic abilities - Attout, Lucie; Majerus, Steve (British journal of developmental psychology, 2018)
Recent studies have demonstrated that both ordinal number processing and serial order working memory (WM) abilities predict calculation achievement. This raises the question of shared ordinal processes operating in both numerical and WM domains. We explored this question by assessing the interrelations between numerical ordinal, serial order WM, and arithmetic abilities in 102 7‐ to 9‐year‐old children. We replicated previous studies showing that ordinal numerical judgement and serial order WM predict arithmetic abilities. Furthermore, we showed that ordinal numerical judgement abilities predict arithmetic abilities after controlling for serial order WM abilities while the relationship between serial order WM and arithmetic abilities was mediated by numerical ordinal judgement performance. We discuss these results in the light of recent theoretical frameworks considering that numerical ordinal codes support the coding of order information in verbal WM. Statement of contribution What is already known on this subject? Numerical ordinal processes predict mathematical achievement in adults. Order WM processing predicts first mathematical abilities. What the present study adds? Numerical ordinal processes predict mathematical achievement in children and independently of order WM. The link between order WM and mathematical abilities was mediated by long‐term ordinal processes.